A lesson before dying - Gaines, Ernest J., 1933-2019. (New York : Vintage Books, 1994)
From the author of, A Gathering of Old Men and The Autobiography of Miss Jane Pittman comes a deep and compassionate novel. Grant Wiggins, a college-educated man returns to 1940s Cajun, he visits and forms an unlikely bond with Jefferson, a young Black man convicted of murder and sentenced to death, for a crime he didn't commit. Together they come to understand the heroism of resisting. Best Books for Young Teen Readers. In the 1940s in rural Louisiana, an uneducated African American man is sentenced to die for a crime he was incapable of committing.
Keywords: African American men -- Fiction; Death row inmates -- Fiction; Race relations -- Fiction; Louisiana -- Fiction; Friendship -- Fiction